(untitled) (Periphērica, 2022)
This collection of nine poems highlights the highly-charged political landscape of Puerto Rico through pointed criticism and poignant nostalgic imagery. Curet follows in the vein of decades of Puerto Rican resistance poetry, and the reality and scope of the nation’s struggle seethes through each line and stanza. These poems are replete with repetition, utilized effectively to illustrate the ongoing instability of the nation across generations.